The Role of Religiosity in the Face of Globalization: A Cross-Cultural Examination - Elias Ahmed; Mahmudulhassan Mahmudulhassan; Muhammad Abuzar; Shikdar Mohammad Riazul (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This qualitative study examines the impact of globalization on religiosity, focusing on how religious beliefs and practices evolve, adapt, or resist change in a rapidly shifting global landscape. Employing a cross-cultural approach, the research explores diverse perspectives through in-depth interviews and thematic analysis. The findings highlight the dynamic interplay between global influences and local religious traditions, revealing varying responses among individuals and communities. While some embrace globalization, integrating new ideas into their faith, others resist or modify their practices to preserve religious identity. This study sheds light on the challenges and opportunities globalization presents for religious communities, offering insights into the ways religious identity is negotiated in an interconnected world.